The Influence of Price, Promotion, And Service Quality on Consumer's Purchase Interest in Matahari Store Department - Hafni Cholida Nasution; Dea Amanda Samosir (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to examine the impact of price, promotion, and service quality on consumer purchase intention at Matahari Department Store. The applied research methodology involves the utilization of a survey approach, wherein questionnaires are distributed to a sample of consumers that has been randomly selected. Regression analysis was employed to examine the gathered data to assess the correlation between the independent factors (pricing, promotion, and service quality) and the dependent variable (buy interest). The research findings demonstrate that consumer buying interest at the Matahari Department Store is significantly influenced by pricing, promotion, and service quality. These several aspects collectively have a role in influencing positive consumer views, leading to an increase in purchase intention. The findings above offer significant insights for shop management in developing enhanced marketing strategies for consumer attraction and satisfaction. The study also emphasizes the significance of retail enterprises in comprehending market dynamics and effectively addressing client demands. The findings of this study have significant practical consequences, indicating that initiatives aimed at increasing customer purchasing interest should consider the appropriate control of prices, the implementation of successful promotional techniques, and the enhancement of service quality. The present study establishes a fundamental basis for informing strategic decision-making processes inside the Matahari Department Store, offering a valuable point of reference for future investigations in this particular domain.